Comparison of clinician diagnosis of COVID-19 with real time polymerase chain reaction in an adult-representative population in Sweden - Quraishi, Eman; Jibuaku, Chiamaka; Lisik, Daniil; Wennergren, Göran; Lötvall, Jan; Nyberg, Fredrik; Ekerljung, Linda; Rådinger, Madeleine; Kankaanranta, Hannu; Nwaru, Bright I. (Respiratory research, 2023)
Background Due to the high transmissibility of SARS-CoV-2, accurate diagnosis is essential for effective infection control, but the gold standard, real-time reverse transcriptase-polymerase chain reaction (RT-PCR), is costly, slow, and test capacity has at times been insufficient. We compared the accuracy of clinician diagnosis of COVID-19 against RT-PCR in a general adult population. Methods COVID-19 diagnosis data by 30th September 2021 for participants in an ongoing population-based cohort study of adults in Western Sweden were retrieved from registers, based on positive RT-PCR and clinician diagnosis using recommended ICD-10 codes. We calculated accuracy measures of clinician diagnosis using RT-PCR as reference for all subjects and stratified by age, gender, BMI, and comorbidity collected pre-COVID-19. Results Of 42,621 subjects, 3,936 (9.2%) and 5705 (13.4%) had had COVID-19 identified by RT-PCR and clinician diagnosis, respectively. Sensitivity and specificity of clinician diagnosis against RT-PCR were 78% (95%CI 77–80%) and 93% (95%CI 93–93%), respectively. Positive predictive value (PPV) was 54% (95%CI 53–55%), while negative predictive value (NPV) was 98% (95%CI 98–98%) and Youden’s index 71% (95%CI 70–72%). These estimates were similar between men and women, across age groups, BMI categories, and between patients with and without asthma. However, while specificity, NPV, and Youden’s index were similar between patients with and without chronic obstructive pulmonary disease (COPD), sensitivity was slightly higher in patients with (84% [95%CI 74–90%]) than those without (78% [95%CI 77–79%]) COPD. Conclusions The accuracy of clinician diagnosis for COVID-19 is adequate, regardless of gender, age, BMI, and asthma, and thus can be used for screening purposes to supplement RT-PCR.